China reform and the role the plan in the 1990s - The International Bank for Reconstruction and Devt.; The International Bank for Reconstruction and Devt. (Washintong, D.C The International Bank for Reconstruction and Devt., 1992)
This report deals with government reforms and development policies in nineties in China
This is a World Bank Country Study
mf 21/01/2019
Ref
Keywords: Economy development; China